The effect of modulators of inflammation on hepatic acute phase proteins and metabolic enzymes - Visser, Jacobus Albertus Koch (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2010.